Incarcerated Littre's hernia: A rare complicated form in a little girl - Othmane alaoui; Abdelhalim Mahmoudi; Khalid Khattala; Youssef Bouabdallah (Elsevier, 2022)
Meckel's diverticulum (MD) is the most common congenital anomaly of the small bowel. Its location in a hernial sac, in particular at the inguinal canal, is uncommon and it is known as Littre's hernia (LH). It's difficult to distinguish from other hernias until complications arise. We report the case of 2-years-old little girl with an incarcerated and strangulated LH at the inguinal region, which was successfully treated by ileal resection and anastomosis followed by hernia repair.